The prospects of cultural exchange to foster the economic relationship between the EU and Korea - Joohyun Go (OrdnungsPolitisches Portal (OPO), 2021)
The goal of this article is to examine the current status of cultural exchanges between Korea and the EU. This paper will examine the extent to which cultural exchanges between the two regions have grown since the adoption of the Korea-EU cultural cooperation protocol in 2011. I will also explore if there are any constraints and if so, possible ways to promote further exchanges in the future. The definition of cultural exchange that this article focuses on is "achieving cultural and economic development by establishing mutual relations with people from other culture." In this context, I carefully examine cultural exchanges that can promote economic exchanges. This is approached from a cultural and diplomatic perspective aimed at capturing the hearts of the other country's general public. To that end, the article looks at two types of cultural exchange support policies at government level. Among them, I particularly focus the agreement on the co-production of audiovisual materials adopted by the "Cultural Cooperation Protocol," which was created as an annex to the Korea-EU FTA. I will then review the current status of exchanges between Korea and Europe in the field of performing arts. Finally, I end by presenting improvement measures and suggestions to expand cooperation in the cultural sector and promote co-production of audiovisual materials. It points out the need for legislative and governance improvements in carrying out government support.
Keywords: 330; Cultural exchange; Cultural Cooperation Protocol; Korea EU cooperation